nevermind I got it.

\((t+1)(3t-3)=(3t-5)(t+2)\)

Expanding gives

\(3t^2-3t+3t-3= 3t^2+6t-5t-10\)

Get the like terms together

\(3t^2-3t^2 -3t+3t +5t - 6t=-10+3\)

3t^{2} cuts out and the remaining equals to -t but u are looking for a positive t so so multiply both sides by (-).

therefore this gives

\(t=10-3\)

\(t=7\)

So on Tuesday, u worked 8 hours and got 18$ and Andrew worked 16 hours and got 9 dollars. And also the question should be

'At the end of the day, I had earned two times more than he had. What is the value of t?'